Peran Dan Implementasi Pengadilan Agama Dalam Melindungi Hak-Hak Perempuan Dan Anak Pasca Perceraian Melalui Putusan Pengadilan Agama Sebagai Upaya Pertahanan Ekonomi Keluarga - Ariani, Taufiqoh Bina; Astawa, I Ketut; Koswara, Indra Yudha (Universitas Medan Area, 2024)
The role and implementation of Religious Courts in protecting the rights of women and children after divorce through religious court decisions as an effort to defend the family's economy. This study aims to understand how religious courts effectively carry out their duties in protecting the rights of women and children and providing economic protection for families after divorce. The research method used in this study is the normative legal research method with a statutory, conceptual, and historical approach. The results of the study indicate that religious courts have a significant role in protecting the rights of women and children after divorce. Religious court decisions consistently apply the principles of justice, benefit and social welfare to ensure that the rights of women and children are well protected. Through these decisions, Religious Court judges as state officials are at the forefront in ensuring that the rights of women and children are protected, as well as providing justice and benefits for providing family economic protection. However, in implementation, not all post-divorce religious court decisions accommodate the rights of women and children. It is hoped that these findings can contribute to the development of better policies in protecting the rights of women and children after divorce, as well as strengthening the role of religious courts as institutions of a legal system that play a role in providing justice and benefits for justice seekers as an effort to defend the family economy after divorce.